Nutritional Habits of Middle School Students in Al-Nasiriyah City - Sara H. Khudair, Wasna J. Mohammed (Pakistan Journal of Medical & Health Sciences, 2022)
Objective(s): The purpose of this study is to ascertain middle school pupils’ nutritional habits. Methodology: The investigation began on November 3rd, 2021 and will conclude on March 10th, 2022. The design is cross-sectional. The study is being undertaken in the male and female middle schools in Al-Nasiryia City. A random sample of 60 middle school pupils is chosen. Consent forms were signed by all students who volunteered to participate in the study. The study will employ a self-report questionnaire separated into two sections: part I will analyze middle school students’ sociodemographic traits, and part II will measure secondary school students’ nutritional knowledge. Content validity and internal consistency reliability are determined using a pilot study. A data collection instrument is employed. The data are analyzed using the descriptive statistical data analysis approach, whereas the data are analyzed using the inferential statistical data analysis approach. Results: Results show that the majority of the female and male students have fair dietary habits (75.0%). Conclusion: The study concluded that nutrition education is an effective strategy for enhancing the dietary habits of middle school students. This study shows that the dietary habits of these students are not affected as they age. Recommendations: The study says that the Ministry of Education should set up nutrition education classes for these students to help them learn more about nutrition-related issues.